2008
DOI: 10.1021/jp8043016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer Nanoparticle Formation on the Efficiency of Polythiophene Based “Bulk-Heterojunction” Solar Cells

Abstract: Polythiophenes are being intensively studied for use in polymer/fullerene bulk-heterojunction photovoltaic (PV) devices because they absorb light throughout the entire visible spectrum and show high hole mobility, which are the two most important parameters for a successful donor in these devices. A large body of anecdotal information exists about what morphological features lead to a high efficiency bulk-heterojunction PV device, but few design parameters for improved polymers exist. We compare two polythioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 37 publications
3
50
0
Order By: Relevance
“…We make this distinction because measuring the overall crystallinity of a BHJ mixture has proven to be very difficult 22 and the packing of polymer domains can be very indefinite, as other studies have shown. 51,52 The TA and SA films are observed to have 62% and 63% aggregated P3HT, respectively, while the Ca capped films both only have ∼50%. It seems as if heating with a metal present causes reduced P3HT aggregation.…”
Section: Describing Morphologymentioning
confidence: 99%
“…We make this distinction because measuring the overall crystallinity of a BHJ mixture has proven to be very difficult 22 and the packing of polymer domains can be very indefinite, as other studies have shown. 51,52 The TA and SA films are observed to have 62% and 63% aggregated P3HT, respectively, while the Ca capped films both only have ∼50%. It seems as if heating with a metal present causes reduced P3HT aggregation.…”
Section: Describing Morphologymentioning
confidence: 99%
“…PQT12 is an interesting high REVIEW mobility polymer which has the same backbone of P3HT, yet its OPV device performs much worse compared to P3HT and in device fabrication, much more amount of PCBM is required. 74,75 Moule et al suggested that the poor connectivity of crystalline nanoparticles could be a reason for its poor performance. PBTTT is another high mobility donor polymer which is similar to PQT12.…”
Section: Nano-fibrillar Devicesmentioning
confidence: 99%
“…[34] Our efforts focused on the idea that we could use conjugated polymers with reduced solubility in what would normally be thought of as good solvents for bulkheterojunction mixtures, such as chlorobenzene (CB) or orthodichlorobenzene (ODCB), to produce high-efficiency as-cast bulk heterojunctions with high crystalline content. We decided to investigate PQT because it is known from the literature to possess a high field-effect mobility [35] and to spontaneously form nanoparticles in solution.…”
Section: The Use Of Polymer Nanoparticlesmentioning
confidence: 99%